Rooftop solar energy awareness on buildings in higher education institutions: Case of Universiti Utara Malaysia - Abualrejal, Hussein Mohammed; Hassan, Mohamad Ghozali; Melan, Mustakim; Pourpunsawat, Pakorn; Al-Rahmi, Waleed Mugahed; Romli, Azizi (PalArch's Journals, 2020)
Rooftop solar energy is a system that is built at the roof of either a residential or commercial building. Many systems can be installed to make rooftop solar energy, with one of them being the photovoltaic (PV) system. The PV system is solar electricity that has been used on buildings owing to the several benefits accorded by it, among which are, cooling the environment in the building, reducing the cost of electricity bill, and facilitating an environment friendly. In order to ensure that rooftop solar energy is widely used, the KeTTHA, under the government, provides a few programs to the society, but regardless of such programs, the majority of people remain unaware of this rooftop solar energy. In this study, the researcher has examined awareness of solar energy among UUM's staff and students. Based on interviews and questionnaire survey, the researcher determined the level of knowledge and information they hold regarding solar energy, in general, and rooftop solar energy, in particular. The study calculated the percentage of awareness among male and female students, after which, the differences between their awareness were obtained. The benefits and methods used to calculate the results were also presented in this study. The results were solely based on the staff and students’ perceptions at UUM. In the future, studies should include a more extensive group from Malaysian society.